Discrepancy Between Perceptions and Reality in Understanding Food Production Systems - UNUK, TATJANA; BEZJAK, VALERIJA; GROBELNIK MLAKAR, SILVA (Anali PAZU HD, 2024)
The study highlights the gap between self-assessed and actual knowledge of Slovenian consumers regarding fruit production systems and their purchasing habits. The research, which involved 248 consumers from various demographic backgrounds, revealed that consumers have a poor understanding of the differences between production systems. The largest gap was observed in the organic system, with 91.5% of respondents believing they were familiar with it, but only 52.0% correctly identifying it. For the integrated and conventional systems, the gap was statistically insignificant. The biodynamic system was correctly identified by 46.0% of respondents, the pesticide-free ("0.0 MRL") system by 52.4%, and the extensive system by 39.9%. Gender, age, and place of residence did not significantly affect correct identification, except in the case of the conventional system, which was better recognized by respondents over 30 years old. Most respondents purchase basic food items in stores (75.4%), while 30.3% buy fruit directly from local producers. Despite a preference for locally and sustainably produced food, consumers did not demonstrate sufficient knowledge of fruit production systems.
Keywords: local production; consumer decisions; fruit production system; shopping habits; sustainable production